Geographic Information System for Mapping and Complaint of Damaged Roads - Winarta, Widiana Putra; Piarsa, I Nyoman; Mandenni, Ni Made Ika Marini (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 9 No 3 (2021): Vol. 9, No. 3, December 2021DO - 10.24843/JIM.2021.v09.i03.p05, 2021)
Indonesia is a massive archipelago of 1.919.400 km², containing roads that span at 542.000 km across various terrain conditions. This diverse geographic environment is a challenge to road constructions and repairs across the country, which has lead to disruption in public service and traffic accidents each year. We propose the Geographic Information System for Mapping and Complaint of Damaged Roads, a solution which can provide users a digital interface to report damaged roads to the transportation department in their area. This research uses Google Maps API to digitize and make a complaint about damaged roads. The result of this research is an android application for the users and a website application for the road managers. The android application is used by the users to make complaints of damaged roads. The web application is used by road managers to draw the road on Google Maps using polyline feature. With this our goal is to systematize the handling of damaged roads information, leading to faster service times and hopefully help reduce the level of traffic accidents in Indonesia. Keywords: Complaint, Damaged road, Geographic Information System, Google Maps, Road  digitization.